PENGARUH HASIL BELAJAR PRODUK KREATIF DAN KEWIRAUSAHAAN TERHADAP MINAT BERWIRAUSAHA SMK IMMANUEL II SUNGAI RAYA - Oktary, Maria Elsy; Ulfah, Maria; Genjik S, Bambang (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aims to determine how the influence of the learning outcomes in the subject of produk kreatif dan kewirausahaan (PKDK) on students’ entrepreneurship interest in class XI Marketing 2 students in SMK Immanuel II Sungai Raya. The research method used was descriptive method with the form of relationship studies. The sample of this study was students of class XI Marketing 2 and the data are gathered from students’ daily tests, especially on the basic competencies in the process of making goods/services products through stages namely stages of containment, stages of formation, stages of assembly and finishing as well as the results of questionnaire distribution to class XI Marketing 2. The results showed that the learning outcomes of produk kreatif dan kewirausahaan (PKDK) subject had an influence on student entrepreneurial interest in Class XI Marketing 2 of SMK Immanuel II Sungai Raya, indicated by the formulation Y = 43,227 + 0,472 X and obtained t count> t table was 2,042 > 2,023. Because t arithmetic> t table Ha is accepted and Ho is rejected, it means there was a positive influence on the learning outcomes of produk kreatif dan kewirausahaan (PKDK) on students’ entrepreneurial interest in class XI Marketing 2 of SMK Immanuel II Sungai Raya. The amount of contribution R square = 0.097, it proved that learning outcomes have an influence on students’ entrepreneurial interest by 9.7%, the rest was influenced by other variables and further research. Keywords: Learning Outcomes, Produk Kreatif dan Kewirausahaan (PKDK, Entrepreneurial Interest